Implementation Of The Provision Of Tenth Decade Remission Based On Presidential Decree No. 174 of 1999 Concerning Remission (Case Study: Law Enforcement and Justice at Gunung Sugih Prison) - Zainuri Zulkarnaen; Baharudin; Tami Rusli; Zainudin Hasan (Cita konsultindo, 2025)
The implementation of the ten-year remission at Gunung Sugih Penitentiary (Lapas) is based on Presidential Decree Number 174 of 1999 concerning Remission. The main focus of this research is on the suitability of the implementation of remission with the principles of justice, particularly the principle of equality before the law . This research aims to identify factors that hinder the implementation of the ten-year remission and evaluate the extent to which the granting process reflects the principles of justice and legal certainty. The researcher used a normative and empirical juridical approach with a descriptive analytical method. The normative juridical approach aims to examine the legal provisions governing remission, while the empirical approach is used to collect data through observation and field studies at Gunung Sugih Penitentiary. The results of this research indicate that the implementation of the ten-year remission has followed procedures in accordance with statutory regulations. Inmates who meet the administrative and substantive requirements are entitled to remission as a form of appreciation for participation in the development program. This process aims to support social rehabilitation and reduce prison sentences. However, implementation in the field still faces obstacles such as limited human resources, a suboptimal inmate data system, and external pressures that affect the objectivity of remission grants. Researchers recommend that prisons improve the quality of human resources, strengthen inmate information and data management systems, and conduct regular evaluations of remission implementation. Continuous outreach to the community is necessary to ensure that remissions are understood as part of the correctional system, not as a disregard for legal justice.